2004
DOI: 10.1016/j.crte.2003.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenic lead mobility in the Shea Creek unconformity-related uranium deposit (Saskatchewan, Canada): migration pathways and Pb loss quantification

Abstract: The average Pb/U ratio of the Shea Creek unconformity-type uranium deposit has been estimated at 0.071 ± 0.015. The calculation was performed on a volume enclosing the orebody to take into account the possible radiogenic lead migration within the ore zone. Despite this precaution, this ratio is significantly lower than the expected ratio (0.211) assuming a main U deposition around 1315 Ma, as suggested by previous U-Pb isotopic dating. Although part of the radiogenic lead can be trapped as galena within the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…14A, B, C), which is expected as the basal Manitou Falls Formation has been a conduit for fluids throughout the history of the basin (Holk et al, 2003). In contrast to what is observed above sandstone-hosted deposits (Holk et al, 2003;Kister et al, 2004), radiogenic Pb is absent in the Manitou Falls Formation sandstones above Millennium (Fig. 14B, C).…”
Section: Implications For Exploration Of Millennium-type Depositsmentioning
confidence: 76%
“…14A, B, C), which is expected as the basal Manitou Falls Formation has been a conduit for fluids throughout the history of the basin (Holk et al, 2003). In contrast to what is observed above sandstone-hosted deposits (Holk et al, 2003;Kister et al, 2004), radiogenic Pb is absent in the Manitou Falls Formation sandstones above Millennium (Fig. 14B, C).…”
Section: Implications For Exploration Of Millennium-type Depositsmentioning
confidence: 76%
“…The age of this mineralized rock is around 1.3 Gy. (Kister, 2003;Kister et al, 2004;Laverret et al, 2010). The sample is cross cut by a one millimetre thick vein of uraninite (UO2, 88.15 wt% U).…”
Section: Methodsmentioning
confidence: 99%
“…Later, Pb isotopes were used for U-mining environmental impact assessment studies. Mining and milling activities have led to the dissemination of radioactive-enriched material containing radiogenic Pb in the environment. The Pb isotope signature of the U-ore can be detected over long distances from the U-mine even after significant mixing with the natural Pb due to the high isotopic contrast between the sources (natural versus U-ore) and to the high radiogenic Pb content of the transported material. Considering a codispersion between radionuclides and Pb originating from the U-mine, Pb isotope fingerprinting allowed highlighting of the dissemination of radionuclide-enriched materials in the environment and calculating their percentage of impact. ,,,,, Pilot studies have also shown the possibility of using Pb isotopes in blood samples as an exposure indicator of U-mine employees on radioactive dusts .…”
Section: Introductionmentioning
confidence: 99%